Advancing Library Services for Mobile Users - Liu, Yan Quan (IGI Global Scientific Publishing, 2025)
As mobile technology becomes integral to everyday life, libraries rework their services to meet the needs of their users. Advancing library services for mobile users requires seamless, intuitive experiences that support research, learning, and engagement. From mobile-friendly catalogs and e-book pla...
Publication Title: https://services.igi-global.com/resolvedoi/resolve.aspx?doi=10.4018/978-1-7998-9175-8
Keywords: dept.ils

A comparison of public library use of statistics – a cross‐country survey report - Liu, Yan Quan (New Library World, 2001)
Librarians have been involved in collecting and disseminating statistics for many years. Utilizing statistics to describe and assess the operation of library activities as a part of library tradition has received growing attention from researchers, policymakers, library managers, and professionals. However, few studies have investigated how statistics are used in libraries. This report compares directors’ uses of statistics provided by national agencies in the USA and China to highlight differences and similarities of the uses the two countries’ directors make of statistics and the statistical information that directors find particular useful. The results are intended to provide library administrators with an insight of how library statistics are used in the managerial process and may also help the national statistical providers to obtain an understanding of the characteristics and pattern of use of their products. © 2001, MCB UP Limited
0 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/154-713-030-974-661 tex.type: [object Object]
Keywords: China; Librarians; Libraries; Management; Statistics; USA; dept.ils

Where does professional education on digital libraries lead our new librarians - Liu, Yan Quan (International Conference on Asian Digital Libraries, 2003)
This study investigates the state of school education for digital libraries. For this study, a web survey was conducted of syllabi of courses on the subject of digital libraries. Similarities and differences on such subjects as teaching emphases, course outlines, textbooks and assignments were compared. The majority of classes now contain a "hands-on" element, a practical component of the course that requires that the students interact with digital libraries. Those students who have received practical experience with digital libraries, like those provided in the "hands-on" courses, are best served for future practice in the field of librarianship. © Springer-Verlag Berlin Heidelberg 2003.
0 citations (Crossref) [2023-10-31] tex.type: Proceedings paper
Keywords: Digital libraries; E-learning; Education; Practical experience; Professional education; School education; Students; Teaching; Web surveys; dept.ils

Is the education on digital libraries adequate - Liu, Yan Quan (New Library World, 2004)
This study investigates the state of education for digital libraries. For this study, a Web survey was conducted of syllabi of courses on the subject of digital libraries (DL). Similarities and differences on such subjects as teaching emphases, course outlines, textbooks and assignments were compared. The majority of classes now contain a “hands-on” element, a practical component of the course that requires that the students interact with digital libraries. Not all of the course contents are up-to-date in the field of library and information technology. While the quality of DL education seems to have advanced at those schools and institutions that offer classes with “hands-on” requirements, the educational approach at many of the “hands-off” universities seems somewhat technophobic and overly dependent on outdated pedagogical methods. Those students who have received practical experience with digital libraries, like those provided in the “hands-on” courses, appear to be best served for future practice in the field of librarianship. © 2004, Emerald Group Publishing Limited
12 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/049-352-432-311-492 tex.type: [object Object]
Keywords: Digital libraries; Europe; Libararies; Library facilities; North America; Surveys; dept.ils

Best practices, standards and techniques for digitizing library materials: a snapshot of library digitization practices in the USA - Liu, Yan Quan (Online Information Review, 2004)
This study investigates current practice in digitizing library materials in the USA. Building a good digital collection has been a common task, pervasive in all types of libraries. Digitization becomes more and more crucial, affecting libraries while they work towards becoming digital. Researchers and practitioners would like to know what practices have been developed to deal with the challenges that pose the most significant problems or concerns for libraries in digitization. Through probing some widespread issues on what materials to digitize, and the associated standards and technologies in digitization in US libraries, this survey of current literature reveals a number of prominent library digitization practices, methods and challenges, and highlights the best practices, trends and interests in library digitization pertaining to both policy and technology marketplace issues.
17 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/059-597-493-339-542 tex.type: [object Object]
Keywords: Analog to digital conversion; Data processing; Digital libraries; Document image processing; Electronic media; Information and Library Science; Multimedia systems; Project management; Public policy; Societies and institutions; Standards; Technical problems; United States of America; dept.ils

The use of statistics in the managerial process by public library directors in China and the USA: a cross‐country survey - Liu, Yan Quan (Library Management, 2001)
Librarians have been involved in collecting and disseminating statistics for many years. Utilising statistics to describe and assess the operation of library activities as a part of library tradition has received growing attention from researchers, policymakers, library managers, and professionals. However, few studies have investigated how statistics are used in libraries. This report compares directors’ uses of statistics provided by national agencies in the USA and China to highlight the differences and similarities between the ways in which the two groups of directors make use of statistics, and the statistical information that directors find particularly useful. The results are intended to provide library administrators with an insight of how library statistics are used in the managerial process, and may also help the national statistical providers to obtain an understanding of the characteristics and pattern of use of their products. © 2001, MCB UP Limited
3 citations (Crossref) [2023-10-31] Citation Key Alias: pop00177 tex.type: [object Object]
Keywords: China; Libraries; Management; Public Libraries; Statistics; USA; dept.ils

Empirical Research for Information Professionals - Liu, Yan Quan (Createspace, 2019)
A collection of empirical research published by Dr. yan Quan Liu and his reasearch teams in the field of information and library science for the 21st-century readers. - Back cover.
Keywords: Case studies; Library science; Research; Library science; dept.ils; faculty_collection

Transforming Library Service for the 21st Century User - Liu, Yan Quan (Createspace, 2018)
This book is a print version of the online course ILS508 User Services. The course content includes the instructor's lecture notes, assignment instructions, assigned readings, discussions an coursework from the students in the classes.
Keywords: Public services (Libraries); dept.ils; faculty_collection

Digital Libraries in Theory and Practices - Liu, Yan Quan (CreateSpace Independent Publishing Platform, 2016)
Keywords: Information storage and retrieval systems; dept.ils; faculty_collection

Library Services for Mobile Users: A Library in the Palm of Your Hand - Liu, Yan Quan (CreateSpace, 2018)
This books is a print version of the online course ILS 440 Information Service Technology offered at Southern Connecticut State University. The course content includes the instructor's lecture notes, assignment instructions, assigned readings, discussions and coursework from students in the classes.
Keywords: Library applications; Public services (Libraries); Mobile communication systems; Technological innovations; dept.ils; faculty_collection

Information Science and Technology: An Introduction for Librarians (course Pack, 2nd Version) - Liu, Yan Quan (Create Space : Yan Quan Liu, 2018)
Keywords: Information science; Information technology; Information and Library Science; dept.ils; faculty_collection

Digital Libraries, Its Theory and Practices. - Liu, Yan Quan (2009)
Thirteen chapters and 47 sections of the book"Digital libraries, its theory and practices" were worked on and the book is ready to send to the publisher. Did a paper that was accepted by the journal Library Hi Tech. Visited China and gave 2 seminars in 2 universities in China.
Keywords: dept.ils; faculty_collection; sabbatical_report

Web 2.0 applications in top Chinese university libraries - Han, Zhiping; Liu, Yan Quan (Library Hi Tech, 2010)
Purpose - This paper aims to explore the status and construction pattern of Web 2.0 technologies employed in top Chinese university libraries, their functionalities and features. Design/methodology/approach - A combination of online survey and content analysis methodology is applied to a sample of 38 top Chinese university libraries' web sites. The Web 2.0 tools are categorized by generally accepted standards with some adjustment for library practices. Data were collected by accessing these university library web sites on two separate occasions during the period of February 10-20, 2009 by utilizing a checklist of 52 questions. Findings - More than two-thirds of the 38 top Chinese university libraries apply one or more kinds of Web 2.0 tools through the basic functions of their web sites. Among six types of tools, Catalog 2.0 and RSS are the most common, while IM, Blog, SNS and Wiki are less frequent. Research limitations/implications - Internal applications that are not publicly accessible contain hidden information that may not be gathered through content analysis since these links usually cannot be found on library web sites. It is difficult to get exact information as to the applications of Web 2.0 in these libraries without an interview method in combination to observation. Originality/value - This study provides an overall picture of Web 2.0 tools developed in top Chinese university libraries, allowing for future evaluation and planning. The implementation of Web 2.0 applications and their constructing pattern is not only indicative of the development of the Chinese digital libraries, but also to their development of digital libraries in the world at large.
48 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/148-213-665-014-156 tex.unique-id: [object Object]
Keywords: China; Digital libraries; University libraries; Worldwide web; dept.ils; peer-reviewed

Web 2.0 applications' usage and trends in top US academic libraries - Boateng, Frank; Liu, Yan Quan (Library Hi Tech, 2014)
Purpose - This paper aims to explore Web 2.0 technologies usage and trends in the top 100 US academic libraries as exemplified through the academic library websites. Design/methodology/approach - The top 100 universities were selected from the US News & World Report's (USNWR) 2013 ranked list's top 100 of the best colleges in the USA. Content analysis was used in terms of quantitative approach. A checklist was developed as the main research instrument based on other checklists and questionnaires. Each of the selected university library websites was visited within a period of two weeks to explore implementation and usage of web tools, including SNS, blog, RSS, wikis, podcast/vodcast, and social bookmarking/tagging. Findings - All 100 academic libraries had a social media presence on Facebook and Twitter, making SNS the most widely applied Web 2.0 tool. The wild was the least applied Web 2.0 technology, with a 34 percent participation rate. Blog was the second most popular tool with a 99 percent participation rate, followed by RSS and IM/Chat with 97 percent and 91 percent respectively. The vodcast and podcast had 47 percent and 46 percent participation rates respectively, while social bookmarking/tagging were also used by 39 percent of the academic libraries. Research limitations/implications - This study is completely based on publicly available data regarding usage of Web 2.0 applications. Web 2.0 tools used on library intranets were not analyzed for this study. Outcomes suggest that academic libraries are increasingly using Web 2.0 applications to promote themselves, enhance library services, and highlight resources to patrons. Originality/value - This is the first research that draws an overall picture of the usage and trends of Web 2.0 applications in the top 100 US academic libraries. This study demonstrates some noticeable patterns regarding usage, trends, and adoption which are relevant to how Web 2.0 applications are perceived and used within academic libraries. The study provides academic libraries with helpful information to better meet their user needs by effectively applying Web 2.0. Additionally, library managers, librarians and other libraries may also find this research beneficial as they plan to deploy Web 2.0.
54 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/000-270-484-139-930 tex.unique-id: [object Object]
Keywords: Academic libraries; Library services; Technology usage; Web 2.0; dept.ils; peer-reviewed

A library in the palm of your hand: mobile services in top 100 university libraries - Liu, Yan Quan; Briggs, Sarah (Information Technology and Libraries, 2015)
What is the current state of mobile services among academic libraries of the country's top 100 universities, and what are the best practices for librarians implementing mobile services at the university level? Through in-depth website visits and survey questionnaires, the authors studied each of the top 100 universities' libraries' experiences with mobile services. Results showed that all of these libraries offered at least one mobile service, and the majority offered multiple services. The most common mobile services offered were mobile sites, text messaging services, e-books, and mobile access to databases and the catalog. In addition, chat/IM services, social media accounts and apps were very popular. Survey responses also indicated a trend towards responsive design for websites so that patrons can access the library's full site on any mobile device. Respondents recommend that libraries considering offering mobile services begin as soon as possible as patron demand for these services is expected to increase.
22 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/012-328-507-257-353 tex.eissn: [object Object] tex.unique-id: [object Object]
Keywords: dept.ils; peer-reviewed

Enhancing digital information access in public libraries - Ayers, Kathleen; Liu, Yan Quan (Proceedings of The Asist Annual Meeting, 2007)
Purpose To explore the impact of public digital library resources on urban residents, to elucidate the current usage patterns of public digital library resources/services and levels of satisfaction with the resources/content in urban digital libraries and make recommendations as to steps that would improve service to this population. Design/Methodology/Approach We conducted an anonymous user-completed survey study of 6 urban libraries to collect demographic and information regarding satisfaction with Digital Library (DL) resource and patterns of use. Findings Our respondents represented a cross section of races, genders, ages, and educational backgrounds. Our results in this much-needed area of study demonstrate that libraries should plan to provide more access, less filtering, regular upgrades, and more training to use the resources. Practical Limitations/Implications Larger studies should be used to follow up this report, in order to be able to obtain a generalized understanding of overall patterns of urban residents using DLs in public settings. Recruitment techniques did not adequately sample potential (but not current) DL users. Originality/Value This study contributes to a scant empirical data set addressing the impact that access to public digital information and services have on urban residents. We offer new data and recommendations that will guide public library administrators in enhancing the impact, efficiency and value of public DL resources/services to improve the digital learning environment for life-long educaiton at all levels in a broad community of urban users.
0 citations (Crossref) [2023-10-31] tex.ids: lens.org/027-715-068-622-316 tex.type: [object Object]
Keywords: dept.ils; ⛔ No DOI found

The impact of digital resource and service use on urban residents in new england public Libraries—A survey report - Liu, Yan Quan; Wnuk, Agnes (Public Library Quarterly, 2009)
Today, access to digital information is essential to patrons using public libraries, whether they have contact with computers at home, work or school or whether the public library is their only contact. In order to evaluate and ultimately enhance public library digital resources and services, it is critical for administrators, librarians and digital information architects to recognize the impact their current digital offerings have on users. This study utilizes a survey to gauge the perceptions of patrons who use digital resources and services in six urban New England public libraries as part of ongoing research into digital information access in public libraries in the United States from the perspective of users.
3 citations (Crossref) [2023-10-31] tex.ids: lens.org/052-608-977-611-377 tex.type: [object Object]
Keywords: Digital divide; Digital libraries; Digital resources; Digital resources services; New England public libraries; Public libraries; Urban libraries; dept.ils; peer-reviewed

Developing an integrated public library service in Dongguan, one of China's fastest growing cities - Liu, Yan Quan; Li, Donglai (New Library World, 2007)
Purpose - The purpose of this case study is to explore the construction pattern and issues involved in the development of an urban library service system in China. Design/methodology/approach - This study was conducted through an analytical evaluation of the development of an integrated public service system and its distribution of information among libraries and information centers in an urban community. Findings - Constructing an integrated public service system is an important trend in urban libraries in the new millennium. Drawing from the Dongguan library's integrated public service system that aims to master better various resources from whole service area, this text summarizes technology innovation and the significant results of the Dongguan library system redevelopment, providing an absorbing insight into developments in the Chinese public library service. Originality/value - While the ultimate goal of integration is to provide better services to meet the information-seeking needs of urban residents, it is necessary to meet these needs through a technological breakthrough in the administration of clustered libraries, to instill a central branch system, and to work out the advantages of group service.
0 citations (Crossref) [2023-10-31] tex.ids: lens.org/074-087-094-612-648 tex.type: [object Object]
Keywords: China; Digital libraries; Library management Public sector organizations; Public libraries; dept.ils

The present and future of China's National Science and Technology Library - A new paradigm of sci-tech information resource sharing - Meng, Liansheng; Liu, Yan Quan (New Library World, 2005)
Purpose - The purpose of this case study is to explore the construction pattern and issues involved with the development of the National Science and Technology Library (NSTL) in China. Design/methodology/approach - This study was conducted through an analytical evaluation of the historical development of scientific and technological information sharing among libraries and information centers and issues around construction of the NSTL. Findings - Since the establishment of its network service system at the end of 2000, the NSTL has made rapid progress in constructing a sci-tech information resource sharing system and offering web-based information services to the patrons of scientific and technical communities all over China. Originality/value - This paper is the first exploration that brings to the forefront the foundational background of the NSTL, the characteristics of its organizational structure, the functions of its service, and the tentative plan to increase its accessibility and usability. Symptomatic of the function of the NSTL constructing pattern will hopefully shed light not only to the reformation of the Chinese sci-tech information management system, but also to the development of scientific digital libraries in the world. © Emerald Group Publishing Limited.
4 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/003-870-955-879-723 tex.type: [object Object]
Keywords: China; Digital libraries; Document management; Information services; National libraries; Worldwide web; dept.ils

Services to mobile users: the best practice from the top-visited public libraries in the US - Liu, Yan Quan; Lewis, Sarah (Information Technology and Libraries, 2023)
Libraries are adapting to the changing times by providing mobile services. One hundred fifty-one libraries were chosen based on circulation, with at least one library or library system from each state, to explore the diverse services provided to mobile users across the United States. According to the data, mobile apps, mobile reference services, mobile library catalogs, and mobile printing are among public libraries’ most-frequently offered services, as determined by mobile visits, content analysis, and librarian survey responses. Every library examined had at least one mobile website, mobile catalog, mobile app, or webpage adapted for a mobile device. Following the COVID-19 outbreak, services such as mobile renewal, subscriber database access, mobile reservations, and the ability to interact with a librarian were expanded to allow better communication with customers—all from the comfort and safety of their own homes. Libraries are continually looking for innovative methods to assist their mobile customers as the world changes.
0 citations (Crossref) [2023-10-31] Number: 1
Keywords: Mobile Apps; Mobile services; Public Libraries; SCSU-student; Survey study; dept.ils; peer-reviewed

International and Comparative Studies in Information and Library Science: A Focus on the United States and Asian Countries - Liu, Yan Quan; Cheng, Xiaojun (Scarecrow Press, 2008)
Keywords: Asia; Asia; Information science; Comparative librarianship; International librarianship; Library science; United States; Information science; United States; Library science; dept.ils; faculty_collection

The use of national public library statistics by public library directors - Liu, Yan Quan; Zweizig, Douglas L (The Library Quarterly, 2001)
7 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/008-574-806-615-498 tex.type: [object Object]
Keywords: dept.ils; ⛔ No DOI found

Public library events: Who, what, where, when, and why? - Kukiolczynski, Katie Teresa; Liu, Yan Quan (Public Library Quarterly, 2021)
An explorative survey pertaining to organization and execution of programs and events offered in public libraries across Connecticut revealed that library programs have been steadily increasing in recent years, with most libraries providing one hundred or more programs a year. The types of programs that are most popular vary throughout the library’s open hours. Children’s programming appears to be more popular during the day while adult programming is more popular in the evening. Program popularity is based on grouping and continuous support from external partners. While this study confirmed that both library space and library staff sizes are adequate for programming, a further investigation would assert that this is the case within nationwide library programming.
1 citations (Crossref) [2023-10-31] Type: Article tex.citation: https://api.elsevier.com/content/abstract/scopus_id/85103569958
Keywords: Connecticut; Public libraries; dept.ils; library events; library programs; peer-reviewed

Adopting Critical Cataloging Practices Post Diversity Audit: Connecting the Community to Your Collection - Anderson, Jessica K.; Liu, Yan Quan (Library Resources & Technical Services, 2025)
To increase patrons’ ability to find resources, it is imperative to investigate barriers and biases in thedescriptive catalog data for inclusive collection management and development standards. This studyused a specially designed descriptive approach to gather quantitative data from 101 public librariansin Connecticut via a Qualtrics survey to identify the key variables that influence the successfulenhancement of online public access catalog (OPAC) metadata after a diversity audit of the librarymaterials. The results revealed factors that promote or impede the integration of inclusive catalogingthat reflects the diversity of the community: (1) appreciating the benefits of audit methods that arefocused on bibliographic records, (2) recognizing the need for buy-in and participation from theentire organization, and (3) stressing the useful integration of institutional and community feedbackto improve the collection’s accessibility and representation. The findings provide practical adviceto public libraries that want to satisfy the diverse demands of their user base by integrating criticalcataloging frameworks into their diversity and inclusion objectives.
Keywords: SCSU-student; dept.ils

Forecasting of Chinese primary energy consumption in 2021 with GRU artificial neural network - Liu, Bingchun; Fu, Chuanchuan; Bielefield, Arlene; Liu, Yan Quan (Energies, 2017)
The forecasting of energy consumption in China is a key requirement for achieving national energy security and energy planning. In this study, multi-variable linear regression (MLR) and support vector regression (SVR) were utilized with a gated recurrent unit (GRU) artificial neural network of Chinese energy to establish a forecasting model. The derived model was validated through four economic variables; the gross domestic product (GDP), population, imports, and exports. The performance of various forecasting models was assessed via MAPE and RMSE, and three scenarios were configured based on different sources of variable data. In predicting Chinese energy consumption from 2015 to 2021, results from the established GRU model of the highest predictive accuracy showed that Chinese energy consumption would be likely to fluctuate from 2954.04 Mtoe to 5618.67 Mtoe in 2021.
55 citations (Crossref) [2023-10-31] Citation Key Alias: ISI:000414578400008 tex.article-number: [object Object] tex.unique-id: [object Object]
Keywords: China; Energy consumption; Energy planning; Energy security; Energy utilization; Forecasting; Forecasting modeling; Forecasting scenarios; Gated recurrent unit; Gross domestic products; Multi-variable linear regression; Multivariable systems; Neural networks; Primary energy consumption; Support vector regression (SVR); dept.ils; energy consumption; energy planning; forecasting scenarios; gated recurrent unit

Are urban public libraries websites accessible to Americans with Disabilities? - Liu, Yan Quan; Bielefield, Arlene; McKay, Peter (Universal Access in the Information Society, 2019)
This paper examines to what extent the 129 members of the Urban Public Libraries Council meet the Section 508 standards for accessibility under the Rehabilitation Act, the minimum acceptable standard for accessibility under the Americans with Disabilities Act. Using an HTML evaluation tool, WAVE, the HTML coding of the libraries’ homepages was evaluated according to the Section 508 criteria for accessibility. After one-to-one deep examination to determine the accessibility of the library websites, the results tended to mirror other studies showing that most library websites have some coding deficiencies that limit the accessibility of the websites. Notably, only 7 of the 122 libraries that were surveyed had no Section 508 errors present with their homepages.
7 citations (Crossref) [2023-10-31] tex.ids: ISI:000461373700014, lens.org/058-290-057-137-474, liuAreUrbanPublic2019 tex.address: [object Object] tex.affiliation: [object Object] tex.author-email: [object Object] tex.da: [object Object] tex.doc-delivery-number: [object Object] tex.eissn: [object Object] tex.journal-iso: [object Object] tex.keywords-plus: [object Object] tex.number-of-cited-references: [object Object] tex.publisher: [object Object] tex.research-areas: [object Object] tex.times-cited: [object Object] tex.type: [object Object] tex.unique-id: [object Object] tex.usage-count-last-180-days: [object Object] tex.usage-count-since-2013: [object Object] tex.web-of-science-categories: [object Object]
Keywords: ADA; Accessibility; Assistive technology; Compliance; Disability; HTML; Impairment; Libraries; Policy; Public libraries; Public library; Public policy; Section 508; Section508; Section 508; Universal usability; Urban libraries; Websites; dept.ils; peer-reviewed

Private post-secondary library websites and the ADA: compliancy and COVID-19 - Bielefield, Arlene; Liu, Yan Quan; Waimon, Victoria (Universal Access in the Information Society, 2023)
This study explores whether US post-secondary institutions (PPI) follow philosophies to foster inclusive communities, providing resources for those individuals with disabilities thrive socially, personally, and academically, while there have been no thorough studies conducted to determine web accessibility of the nation’s top-ranked PPI library webpages. Additionally, this study pioneers in comparison with the accessibility of PPI’s library homepages fighting COVID-19. The study evaluated the library homepages of the premium PPIs based on Money.com’s 2019 list of “The Best Colleges in America” via the WAVE web accessibility evaluation tool. The outcomes determined that most of the library homepages analyzed were littered with numerous errors, and the shift to online-based research in learning had no significant impact on the number of errors WAVE detected. The disconcerting findings of this study demonstrate the overall failure to recognize the importance of web accessibility or perhaps even the indifference toward accessibility on the part of the PPI community.
Keywords: ADA; Academic libraries; Accessibility; COVID-19; Disability; Overall failure; Philosophical aspects; Post-secondary institutions; Private colleges and universities; SCSU-student; Section 508; WAVE; WCAG; Web accessibility; Websites; dept.ils; peer-reviewed

Exploring library core competencies: A text mining study of american library association’s job advertisements from 2006 through 2017: - Yang, Qinghong; Shi, Zehong; Liu, Yan Quan (Social Science Computer Review, 2021)
Are core competency requirements for relevant positions in the library shifting? Applying natural language processing techniques to understand the current market demand for core competencies, this study explores job advertisements issued by the American Library Association (ALA) from 2006 to 2017. Research reveals that the job demand continues to rise at a rate of 13% (2006–2017) and that the requirements for work experience are substantially extended, diversity of job titles becomes prevalent, and rich service experience and continuous lifelong learning skills are becoming more and more predominant for librarians. This analytical investigation informs the emerging demands in the American job market debriefing the prioritization and reprioritization of the current core competency requirements for ALA librarians. © The Author(s) 2021.
0 citations (Crossref) [2023-10-31]
Keywords: dept.ils; peer-reviewed

Academic pursuits and involvement in decision-making: study on the formation of U.S. university think tanks - Lyu, Qing; Bielefield, Arlene; Liu, Yan Quan (Administrative Sciences, 2023)
This paper analyzes the concept of think tanks and concludes that think tanks have three basic characteristics. Firstly, they are based on academic research, relatively independent operation, and aim to serve scientific decision-making. Taking Ivy League think tanks as an example, this paper provides a preliminary discussion of ways for think tanks to maintain the scientific nature of their research, maintain the independence of their operations, and disseminate research results to enhance their influence. It covers institutional mission, research team construction, institutional governance, fundraising, achievements and activities, and alumni networks. This paper proposes a framework of university think tank generation paths associated with the essential characteristics of think tanks. The paper points out that, as a research consulting organization grown out of universities, university think tanks must maintain the scientific nature and independence of research while providing support and services for decision-making. Only in this way can they truly serve scientific and democratic decision-making, gain the trust of the public and have a real lasting influence.
0 citations (Crossref) [2023-10-31] Number: 3
Keywords: American university affiliated think tank; characteristics of think tank; decision-making; dept.ils; peer-reviewed; the ivy league university; think tank operation mechanism

ADA digital accessibility on academic library websites - Liu, Yan Quan; Bielefield, Arlene; Beckwith, Jennifer (College & Research Libraries, 2024)
Studying ADA accessibility at library websites of top universities selected from the U.S. News and World Report, the authors used WAVE and AChecker to assess data in compliance with WCAG 2.0 standards. Almost 8 out of 10 public university academic libraries reported accessibility errors as one of the major findings. Low color contrast was becoming a more commonly occurring accessibility issue, making it difficult for people with vision impairments to perceive the color of the image. The outcomes of the study suggest that academic libraries around the world should continue improving their website accessibility.
Keywords: SCSU-student; dept.ils; peer-reviewed

The provision of mobile services in US urban libraries - Guo, Ya Jun; Liu, Yan Quan; Bielefield, Arlene (Information Technology and Libraries, 2018)
To determine the present situation regarding services provided to mobile users in US urban libraries, the authors surveyed 138 Urban Libraries Council members utilizing a combination of mobile visits, content analysis, and librarian interviews. The results show that nearly 95% of these libraries have at least one mobile website, mobile catalog, or mobile app. The libraries actively applied new approaches to meet each local community’s remote-access needs via new technologies, including app download links, mobile reference services, scan ISBN, location navigation, and mobile printing. Mobile services that libraries provide today are timely, convenient, and universally applicable.
3 citations (Crossref) [2023-10-31] Citation Key Alias: ISI:000435630900009, lens.org/084-687-778-320-226 tex.eissn: [object Object] tex.unique-id: [object Object]
Keywords: dept.ils; human; mobile application; peer-reviewed; printing; publication; review

Effect of different areal precipitation estimation methods on the accuracy of a reservoir runoff inflow forecast model - Zhong, Wei; Li, Ruirui; Liu, Yan Quan; Xu, Jin (IOP Conference Series: Earth and Environmental Science, 2018)
Areal precipitation estimation directly affects the accuracy of reservoir runoff inflow forecasts and flood dispatching decision-making. Because of the heterogeneous spatial and temporal precipitation distributions in large basins, inadequate precipitation stations normally have a negative impact on forecast accuracy. Using the Panjia-kou reservoir runoff inflow forecast as the research subject, this paper adopts the Thiessen polygon block, square grid computing, and DEM (digital elevation model) methods to estimate average regional areal precipitation. Based on the estimation, a model for the Panjia-kou reservoir runoff forecast is developed. The results indicate that different areal precipitation estimation methods have significantly different effects on the accuracy of the reservoir runoff inflow forecast. When the average regional precipitation estimation from the DEM method is used as an input to the model, the simulation results are accurate and are much better than those from the other two average regional precipitation estimation methods.
2 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/009-272-786-643-178, pop00315
Keywords: Air pollution; Areal precipitation; Decision making; Different effects; Digital elevation model; Forecast accuracy; Forecasting; Grid computing; Precipitation distribution; Precipitation estimation; Research subjects; Reservoirs (water); Runoff; Runoff forecast; Surveying; dept.ils

Current market demand for core competencies of librarianship-a text mining study of american library association's advertisements from 2009 through 2014 - Yang, Qinghong; Zhang, Xingzhi; Du, Xiaoping; Bielefield, Arlene; Liu, Yan Quan (Applied Sciences-Basel, 2016)
As librarianship evolves, it is important to examine the changes that have taken place in professional requirements. To provide an understanding of the current market demand for core competencies of librarianship, this article conducts a semi-automatic methodology to analyze job advertisements (ads) posted on the American Library Association (ALA) Joblist from 2009 through 2014. There is evidence that the ability to solve unexpected complex problems and to provide superior customer service gained increasing importance for librarians during those years. The authors contend that the findings in this report question the status quo of core competencies of librarianship in the US job market.
23 citations (Crossref) [2023-10-31] tex.article-number: 48 tex.unique-id: ISI:000371827200001
Keywords: Competency; Job advertisement; Librarianship; Text mining; dept.ils; peer-reviewed

Digital information access in urban/suburban communities: A survey report of public digital library use by the residents in Connecticut - Liu, Yan Quan; Martin, Craig; Roehl, Eileen; Yi, Zhixian; Ward, Sheila (OCLC Systems and Services, 2006)
Purpose - The purpose of this paper is to explore the impact of public digital services on urban/suburban residents, to uncover the current usage of public digital services and levels of satisfaction with the digital resources/content in urban digital libraries (networked computers with specific information infrastructure designed free for public use). Design/methodology/approach - A qualitative approach is used as a main stream in the research framework as the method of inquiry. Qualitative one-to-one interviews include surveying users who use public library websites, observing the users, consulting librarians about the users, and interviewing the users. Findings - Provides demographic patterns of the patron's interaction with the digital services public libraries provide, and the satisfaction and compliances the residents have regarding information access through the digital technology in urban/suburban Connecticut. Practical implications - Because of the small number of participants, this study has limitations in being generalized to an understanding of overall patterns of urban residents using digital resources in public settings in the USA or elsewhere, however, it could be a good pilot study for a nation-wide survey with the methods tested. Originality/value - This study helps fulfill the scant empirical attention given to the impact access to public digital information or use of digital library services on the urban/suburban residents, offers new data that help public library administrators enhance the impact, efficiency and value of the public digital library services to improve the digital learning environments for life-long education at all levels in a broad community of urban-suburban users. © Emerald Group Publishing Limited.
5 citations (Crossref) [2023-10-31] tex.ids: lens.org/051-401-327-795-077 tex.type: [object Object]
Keywords: Design/methodology/approach; Digital learning environment; Digital libraries; Digital technologies; Information retrieval; Information services; Information studies; Life-long educations; Public libraries; Public library; Qualitative approach; Specific information; Surveys; dept.ils

The provision of patron services in Chinese academic libraries responding to the COVID-19 pandemic - Guo, Yajun; Yang, Zinan; Yang, Zhishun; Liu, Yan Quan; Bielefield, Arlene; Tharp, Gregory (Library Hi Tech, 2020)
Purpose: The purpose of this paper is to identify the measures employed in the provision of patron services in Chinese academic libraries responding to the COVID-19 pandemic, noting the challenges and issues inherent in providing substantial services while undergoing a public health emergency. Design/methodology/approach: This paper uses an analytical survey study of 137 Chinese academic libraries using data collected through a combination of website investigation, social media access and direct correspondences. Findings: Over 94% of Chinese academic libraries released COVID-19-related information through their websites; the majority switched their service focus to partly or solely remotely online, including remote access, free electronic resources, virtual references reachable 24/7 and research support services deliverable online; services of print materials were altered to e-books for conveniences. Research limitations/implications: It should be noted that the survey was conducted from February 12 to April 5, 2020; because of the rapid updates to the library's website and social media channels, the status of their patron services are in the process of dynamic changes and that there should be many libraries that have adopted some patron service methods, but this study is difficult to cover comprehensively. In addition, patron services carried out offline by the surveyed libraries but not disclosed on the online platform could not be analyzed in a way that would be consistent with the data provided by the survey. Originality/value: By providing evidence of the current status of patron services in Chinese academic libraries during the COVID-19 pandemic, this study helps fulfill the scant empirical attention given to the impact of nationwide public health crises on academic libraries and offers new data of the best practices that help library administrators enhance the impact, efficiency and value of library services to their target community users. © 2020, Emerald Publishing Limited.
32 citations (Crossref) [2023-10-31] tex.ids: guoProvisionPatronServices2020a tex.citation: https://api.elsevier.com/content/abstract/scopus_id/85088570958 type: Article
Keywords: Academic libraries; COVID-19; China; Patron services; Survey; Virtual services; dept.ils; peer-reviewed